Hungarian National Ballet Recent Review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Hungarian National Ballet, "Mayerling", Kenneth MacMillan.
Dentro del apartado "Dance Now. Recent Reviews".